Project level Women's Empowerment in Agriculture Index for Market Inclusion used to inform gender strategies for three value chains in Honduras - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Swisscontact used pro-WEAI+MI to inform gender strategies for three value chains in Honduras.